2006
DOI: 10.1073/pnas.0603974103
|View full text |Cite
|
Sign up to set email alerts
|

An arsenic metallochaperone for an arsenic detoxification pump

Abstract: Environmental arsenic is a world-wide health issue, making it imperative for us to understand mechanisms of metalloid uptake and detoxification. The predominant intracellular form is the highly mephitic arsenite, which is detoxified by removal from cytosol. What prevents arsenite toxicity as it diffuses through cytosol to efflux systems? Although intracellular copper is regulated by metallochaperones, no chaperones involved in conferring resistance to other metals have been identified. In this article, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
160
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(163 citation statements)
references
References 30 publications
2
160
0
1
Order By: Relevance
“…We analyzed the distribution of more than 100 arsI genes and found that all are in ars operons. There seems to be no specific ars gene associated with arsI, in contrast to arsD and arsA, which always go together because their functions are interrelated (32). MerB is a C·Hg lyase that confers resistance to organomercurials (33).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the distribution of more than 100 arsI genes and found that all are in ars operons. There seems to be no specific ars gene associated with arsI, in contrast to arsD and arsA, which always go together because their functions are interrelated (32). MerB is a C·Hg lyase that confers resistance to organomercurials (33).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, structural characterization of substrate and product complexes of the arsenate reductase ArsC, which reduces arsenate (AsO 4 3Ϫ ) to arsenite (AsO 2 Ϫ ), has helped elucidate this step of the arsenic detoxification pathway (3,4). Recent studies of E. coli ArsD indicate that it is a metallochaperone, transporting As(III) to ArsA for extrusion (5). Extended x-ray absorption fine structure and mutagenesis studies have shown that ArsR coordinates As(III) with three cysteine thiolates at a distance of 2.25 Å, a coordination mode that ArsD is also proposed to employ (1,5).…”
mentioning
confidence: 99%
“…Recent studies of E. coli ArsD indicate that it is a metallochaperone, transporting As(III) to ArsA for extrusion (5). Extended x-ray absorption fine structure and mutagenesis studies have shown that ArsR coordinates As(III) with three cysteine thiolates at a distance of 2.25 Å, a coordination mode that ArsD is also proposed to employ (1,5). However, no x-ray or NMR structures of ArsR, the repressor protein, or ArsD have been reported to date.…”
mentioning
confidence: 99%
“…However, based on the current evidence, limitation of As uptake is apparently not the way for P. vittata to tolerate high levels of As in the growth conditions because no altered (94) arsenate/phosphate uptake kinetics was detected in the stressed P. vittata (26). Arsenite extrusion as in E. coli (30) is also unlikely a tolerance mechanism for P. vittata. Compartmentation of toxic As into vacuoles of the target cells, such as fronds (27,31,32) and trochome cells (20), after its rapid uptake and translocation should be a key mechanism of As tolerance in this fern although the detailed mechanisms underlying As tolerance in P. vittata are largely unknown.…”
Section: P Vittata Is Hypertolerant To Asmentioning
confidence: 77%